Composite protective layer for battery, preparation method of composite protective layer and method for improving impact resistance of battery main body
By applying a composite protective layer outside the battery, the problem of poor impact resistance of the battery is solved, and higher impact absorption and puncture resistance are achieved, improving the safety of the battery.
Patent Information
- Application Number
- CN202411933628.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-14
AI Technical Summary
When existing batteries are severely impacted or squeezed, they have poor impact resistance, prone to short circuit or damage, and lack of safety.
A composite protective layer is provided, including an optional barrier layer, a non-Newtonian fluid material layer and an absorbent layer, and an absorbent layer composed of a fiber reinforced resin-based composite material, prepared by a hot pressing process.
This composite protective layer can effectively improve the impact absorption capacity and puncture resistance of the battery body, prevent the battery from short circuit or damage during violent impact or squeeze, and improve the safety of the battery.
Smart Images

Figure CN119610804A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite protective layer for batteries and a preparation method thereof, and a method for improving the impact resistance of a battery body. Background Art
[0002] With the continuous development of the pure electric vehicle industry, the safety of power battery packs has received increasing attention. Impacts from road splashes and obstacles may cause damage to the battery and potential safety hazards. Existing lithium battery protection structures mostly use a single material or a simple composite structure. The power battery box relies on a metal box made of aluminum profiles or sheet metal to resist impact; the impact force between the battery cells is buffered by structures such as polyurethane foam and ceramic silicon-based glass fiber composite materials. These structures often cannot effectively absorb and disperse the impact force when facing severe impact or extrusion, resulting in battery damage or short circuit.
[0003] CN221176415U discloses a battery cell, a battery, a battery pack and an electrical device, wherein the battery cell comprises a battery cell body; a flexible protective film, wherein the flexible protective film comprises an inner protective film and an outer protective film, wherein the inner protective film is coated on the battery cell body, the outer protective film is arranged on the outer side of the inner protective film, and a receiving cavity is formed between the outer protective film and the inner protective film; and a protective body, wherein the protective body has non-Newtonian fluid characteristics and is filled in the receiving cavity. Although the viscosity of this structure increases sharply when subjected to a large force, thereby improving the safety of the battery cell, the protective effect is single, and it is difficult to provide effective protection, and there is no effective buffering effect during impact.
[0004] CN220021408U discloses a protective plate, including a metal layer, a first protective layer and a second protective layer, wherein the first protective layer and the second protective layer respectively include a network structure and a seal, wherein the network structure has a mesh, wherein a shear thickening fluid is distributed in the mesh, and wherein the seal seals and covers the network structure and the shear thickening fluid. This application fills the mesh of the network structure with a shear thickening fluid for phase change energy absorption, which can absorb part of the impact force. However, the protective layer is in a flowing liquid state, and the protection method is single, resulting in poor effect. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of poor impact resistance and insufficient safety of batteries in the prior art, and to provide a composite protective layer for a battery and a preparation method thereof, as well as a method for improving the impact resistance of a battery body. The composite protective layer applied to the outside of the battery can effectively prevent the battery from short-circuiting or being damaged when subjected to severe impact or extrusion.
[0006] In order to achieve the above objectives, the present invention provides a composite protective layer for a battery, the composite protective layer comprising an optional barrier layer, a non-Newtonian fluid material layer and an absorption layer arranged in sequence, and the absorption layer comprises a fiber-reinforced resin-based composite material.
[0007] The second aspect of the present invention provides a method for preparing the above-mentioned composite protective layer for a battery pack, comprising: coating a non-Newtonian fluid material on the surface of the absorption layer, and then optionally compounding a barrier layer on the surface of the non-Newtonian fluid material, and then hot pressing.
[0008] The third aspect of the present invention provides a method for improving the impact resistance of a battery body, comprising: compounding the composite protective layer for a battery described in the first aspect on the outer surface of the battery body;
[0009] Preferably, the battery body is a battery cell, a soft-pack battery, a battery module or a battery PACK.
[0010] The composite protective layer provided by the present invention utilizes the synergistic effect of the non-Newtonian fluid material layer and the absorption layer arranged in sequence. When the composite protective layer is applied to the outside of the battery body, it can not only improve the impact absorption capacity of the battery body, but also show a synergistic enhancement effect in puncture protection, and can effectively prevent the battery from short-circuiting or being damaged when it is subjected to severe impact or extrusion. Therefore, the composite protective layer provided by the present invention provides more effective external protection for batteries, especially lithium battery cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 is a schematic diagram of the structure of the composite protective layer on the outer surface of the battery body in the present invention;
[0012] Figure 2 is the puncture test result of the soft pack battery using the composite protective layer of Example 1;
[0013] Figure 3 This is the puncture test result of the soft-pack battery using the composite protective layer of Comparative Example 1;
[0014] Figure 4 This is the puncture test result of the soft-pack battery using the composite protective layer of Comparative Example 2.
[0015] Description of Reference Numerals
[0016] 1 barrier layer, 2 non-Newtonian fluid material layer, 3 absorption layer DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] A first aspect of the present invention provides a composite protective layer for a battery, the composite protective layer comprising an optional barrier layer, a non-Newtonian fluid material layer and an absorption layer arranged in sequence, the absorption layer comprising a fiber-reinforced resin-based composite material.
[0019] In the present invention, by utilizing the synergistic effect of the non-Newtonian fluid material layer and the absorption layer arranged in sequence, when the composite protective layer is applied to the outside of the battery body, it can not only improve the impact absorption capacity of the battery body, but also show a synergistic enhancement effect in puncture protection, and can effectively prevent the battery from short-circuiting or being damaged when subjected to severe impact or extrusion.
[0020] According to some preferred embodiments of the present invention, the thickness ratio of the non-Newtonian fluid material layer to the absorption layer is 1-20:1, which can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1 or any range between the two. Preferably, the thickness ratio of the non-Newtonian fluid material layer to the absorption layer is 6-14:1. Controlling the thickness ratio of the non-Newtonian fluid material layer and the absorption layer within the above preferred range is conducive to further exerting the synergistic effect of the non-Newtonian fluid material layer and the absorption layer, and the impact absorption capacity and anti-puncture effect are better; if the relative thickness of the non-Newtonian fluid material layer is too low, the anti-impact performance of the battery core cannot achieve the expected effect, and if the relative thickness is too high, the total weight of the battery is too high.
[0021] In the present invention, the barrier layer is used to prevent the non-Newtonian fluid from directly contacting the surface of the battery body. Those skilled in the art can choose to set or not set the barrier layer as needed, both of which can play a role in improving the impact resistance of the battery body. Preferably, along the surface of the battery body outward, the composite protective layer includes a barrier layer, a non-Newtonian fluid material layer and an absorption layer arranged in sequence. The use of the above preferred embodiment is conducive to improving the impact absorption capacity of the battery body while preventing non-Newtonian fluid materials or tiny particles from penetrating and directly contacting the battery, thereby reducing safety risks.
[0022] According to the present invention, the barrier layer is a flexible film, preferably selected from flexible films such as diaphragms. The diaphragm can be any conventional flexible diaphragm or nanocomposite diaphragm in the art, for example, a ceramic diaphragm, a fiber diaphragm, a polyimide film, etc. According to the present invention, preferably, the melting point of the barrier layer is not less than 130°C, preferably not less than 180°C, and more preferably not less than 200°C. If the melting point of the barrier layer is too low, the diaphragm will melt and deform when the battery is in a high temperature environment or locally hot, destroying the three-layer structure, thereby causing direct contact between the non-Newtonian and the battery, causing unnecessary safety hazards or reducing the protective effect of the three-layer structure. The above preferred situation is conducive to further reducing safety risks at high temperatures.
[0023] According to some preferred embodiments of the present invention, the longitudinal tensile strength MD of the barrier layer is ≥80Mp, for example, 85Mp, 90Mp, 95Mp, 100Mp, preferably 80-100Mp.
[0024] Preferably, the transverse tensile strength TD of the barrier layer is ≥50 Mp, for example, 60 Mp, 70 Mp, 80 Mp, 90 Mp, 100 Mp, preferably 50-100 Mp.
[0025] In the present invention, the tensile strength is measured by the GB / T1040.3-2006 method.
[0026] In the present invention, the thickness of the barrier layer is relatively small. Preferably, the thickness of the barrier layer is 0-100 μm, preferably 5-20 μm, for example, it can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 μm or any range between two specific thickness values. Controlling the thickness of the barrier layer within the above range is not only beneficial to the cyclic expansion effect during the operation of the battery, but also can reduce the overall thickness of the three-layer structure.
[0027] In the present invention, the non-Newtonian fluid material layer includes a non-Newtonian fluid material. In the present invention, the "non-Newtonian fluid material" has a conventional definition in the art, and refers to a fluid that does not satisfy the Newtonian viscosity experimental law.
[0028] According to the present invention, preferably, the peak storage modulus of the non-Newtonian fluid material is 1×10 5 -5×10 6 Pa, preferably 2×10 5 -3×10 6 Pa.
[0029] According to the present invention, preferably, the peak loss modulus of the non-Newtonian fluid material is 2×10 4 -3×10 5 Pa, preferably 3×104 -2×10 5 Pa.
[0030] In the present invention, the peak storage modulus and the peak loss modulus of the non-Newtonian fluid material are obtained by analyzing with a rotational rheometer, and the shear rate is 0.1-100 Hz.
[0031] In the present invention, preferably, the thickness of the non-Newtonian fluid material layer is 2-10mm, for example, it can be 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm and other specific thickness values or any range between two. Preferably, the thickness of the non-Newtonian fluid material layer is 2-6mm. Controlling the thickness of the non-Newtonian fluid material layer within the above preferred range is conducive to further improving the impact resistance of the battery body. If the thickness of the non-Newtonian fluid layer is too low, the impact resistance may be weak, and if the thickness is too high, the total weight of the battery may be too high. The overall weight of the battery is large, which will not only increase the energy consumption of the whole vehicle, but also reduce the cruising range, and affect the vehicle's handling and load-carrying capacity.
[0032] In the present invention, a micrometer screw is used to measure the thickness of the non-Newtonian fluid material layer.
[0033] The present invention has a wide range of selection for the specific composition of the non-Newtonian fluid material, and those skilled in the art can make a selection according to actual needs, preferably based on satisfying the above-mentioned physicochemical properties.
[0034] According to some preferred embodiments of the present invention, the non-Newtonian fluid material comprises reinforcing particles, pyroboric acid, hydroxy silicone oil and oleic acid. All of the above materials can be obtained commercially. The pyroboric acid can also be prepared by heating boric acid at 104-200°C.
[0035] Preferably, the particle size of the reinforcing particles is 0.1-0.5 μm, preferably 0.2-0.4 μm.
[0036] Preferably, the specific surface area of the reinforced particles is 100-300m 2 / g, preferably 150-250m 2 / g.
[0037] According to the present invention, preferably, the reinforcing particles are selected from at least one of silica particles, calcium carbonate, titanium powder, polystyrene (PS) and polymethyl methacrylate (PMMA), preferably silica particles.
[0038] According to some preferred embodiments of the present invention, the mass ratio of the reinforcing particles, pyroboric acid, and hydroxy silicone oil is 1: (0.1-5): 5-50, preferably 1: (0.5-2): 10-30, for example, it can be 1: 0.5: 10, 1: 1: 10, 1: 1: 20, 1: 1: 30, 1: 2: 10, 1: 2: 20, 1: 2: 30, etc., or any range between the two. The use of the non-Newtonian fluid material of the preferred composition is conducive to further exerting the synergistic effect of the non-Newtonian fluid material layer and the absorption layer, and further improving the impact absorption capacity and puncture resistance of the battery body.
[0039] Preferably, the content of oleic acid is 0.2-2 mL relative to the total amount of 100 g of reinforcing particles, pyroboric acid, and hydroxy silicone oil, for example, it can be 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2 mL or any range therebetween. Preferably, the content of oleic acid is 0.5-1 mL relative to the total amount of 100 g of reinforcing particles, pyroboric acid, and hydroxy silicone oil.
[0040] According to the present invention, the absorption layer comprises a fiber-reinforced resin-based composite material.
[0041] According to some preferred embodiments of the present invention, the density of the fiber-reinforced resin-based composite material is 1.2-2.2 g / cm 3 , preferably 1.3-2g / cm 3 .
[0042] According to some preferred embodiments of the present invention, the fiber-reinforced resin-based composite material has a tensile strength of 4-10 GPa and a modulus of 100-300 GPa.
[0043] Any fiber-reinforced resin-based composite material in the art can be applied to the present invention, for example, it can be at least one of PBO fiber, glass fiber, and carbon fiber. Preferably, the fiber-reinforced resin-based composite material is PBO fiber.
[0044] According to the present invention, preferably, the thickness of the absorption layer is 0.1-10 mm, preferably 0.1-1.5 mm, for example, it can be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm or other specific thickness values or any range between two thereof.
[0045] In the present invention, a fiber-reinforced resin-based composite material having the above-mentioned preferred thickness can be directly obtained from commercial sources and used directly as the absorption layer, or the fiber-reinforced resin-based composite material can be made into an absorption layer having the above-mentioned thickness by any molding method in the art, and those skilled in the art can make the selection according to actual conditions.
[0046] The second aspect of the present invention provides a method for preparing the composite protective layer for a battery pack, comprising:
[0047] The non-Newtonian fluid material is coated on the surface of the absorption layer, and then a barrier layer is optionally compounded on the surface of the non-Newtonian fluid material, and then heat pressing is performed.
[0048] In the present invention, by coating the non-Newtonian fluid material on the surface of the absorption layer, the thickness and uniformity of the non-Newtonian fluid material can be ensured, thereby further improving the impact resistance of the prepared composite protective layer.
[0049] According to some preferred embodiments of the present invention, the method for preparing the non-Newtonian fluid material comprises: first mixing the reinforcing particles, pyroboric acid, and hydroxy silicone oil under stirring conditions, and then second mixing them with oleic acid.
[0050] The reinforcing particles, pyroboric acid, hydroxy silicone oil and oleic acid are the same as those defined in the first aspect and will not be described in detail herein.
[0051] According to the present invention, preferably, the mass ratio of the reinforcing particles, pyroboric acid and hydroxy silicone oil is 1:(0.1-5):5-50, preferably 1:(0.5-2):10-30.
[0052] Preferably, the temperature of the first mixing is 150-300° C., preferably 180-260° C., and the time is 60-480 min, preferably 120-240 min.
[0053] Preferably, the stirring speed is 5-200 r / min, preferably 10-50 r / min.
[0054] Preferably, the hot pressing conditions include: a temperature of 60-200° C., preferably 100-150° C.; and / or a pressure of 0.2-1 MPa, preferably 0.3-0.8 MPa, and / or a holding time of 100-1000 s, preferably 200-800 s.
[0055] The third aspect of the present invention provides a method for improving the impact resistance of a battery body, comprising: composite the composite protective layer for the battery described in the first aspect onto the outer surface of the battery body.
[0056] The method provided by the present invention can be applied to any battery body in the art, for example, a battery cell, a soft-pack battery, a battery module or a battery PACK package.
[0057] The present invention has no particular limitation on the battery material system to which the battery body belongs, and a lithium battery is preferred.
[0058] The present invention will be described in detail below through examples.
[0059] The raw materials used in the following examples are as follows:
[0060] The silica particles were purchased from a commercial source, with an aggregate particle size of about 0.2-0.3 μm, a specific surface area of 200 m2 / g, and a density of 36.8 kg / m3;
[0061] Hydroxyl silicone oil (PDMS), commercially available, specification 1500 cP.
[0062] PBO fiber material, commercially available, density 1.56 g / cm 3 , thickness is 0.3mm.
[0063] The diaphragm is a commercial PI diaphragm with a thickness of 12 μm and a density of 0.8 g / cm 3 The operating temperature range is 160-350℃, no thermal shrinkage will occur at 180℃, the tensile strength MD≥90Mp, TD≥60Mp.
[0064] Example 1
[0065] (1) Boric acid was heated to 180°C and kept warm for 2 hours to prepare pyroboric acid. Pyroboric acid, silicon dioxide and hydroxy silicone oil were then mixed in a mass ratio of 1:1:20 to obtain 110 g of the mixture, which was reacted in an oven at 200°C for 3 hours with a stirring rate of 15 r / min. Finally, 1 mL of oleic acid was added to the reaction mixture as a plasticizer to obtain a non-Newtonian fluid material.
[0066] The rotational rheometer was used for measurement, and the shear rate was set at 0.1-100 Hz. The peak storage modulus of the non-Newtonian fluid material was 2.1×10 6 Pa, peak loss modulus 1.7×10 5 Pa.
[0067] (2) coating the obtained non-Newtonian fluid material onto the PBO fiber material layer, and then covering the surface of the non-Newtonian fluid material with a PI diaphragm, and using a hot pressing process (105° C., 0.6 MPa, and holding time of 600 s) to form a three-layer composite structure;
[0068] Among them, the thickness of the barrier layer is 12μm; the thickness of the non-Newtonian fluid material layer is 3mm; and the thickness of the absorption layer is 0.3mm.
[0069] Example 2
[0070] (1) Boric acid was heated to 180°C and kept warm for 2 hours to prepare pyroboric acid. Then pyroboric acid, silica and hydroxy silicone oil were mixed in a mass ratio of 1:2:20 to obtain 115 g of the mixture, which was reacted in an oven at 200°C for 3 hours with a stirring rate of 15 r / min. Finally, 1 mL of oleic acid was added to the reaction mixture as a plasticizer to obtain a non-Newtonian fluid material; the peak storage modulus of the non-Newtonian fluid reached 2.2×10 5 Pa, peak loss modulus 3.1×10 4 Pa.
[0071] (2) coating the obtained non-Newtonian fluid material onto the PBO fiber material layer, and then covering the surface of the non-Newtonian fluid material with a PI diaphragm, and using a hot pressing process (105° C., 0.6 MPa, and holding time of 600 s) to form a three-layer composite structure;
[0072] Among them, the thickness of the barrier layer is 12μm; the thickness of the non-Newtonian fluid material layer is 2mm; and the thickness of the absorption layer is 0.3mm.
[0073] Example 3
[0074] (1) Boric acid was heated to 180°C and kept warm for 2 hours to prepare pyroboric acid. Then pyroboric acid, silica and hydroxy silicone oil were mixed in a mass ratio of 2:1:20 to obtain 115 g of the mixture, which was reacted in an oven at 200°C for 3 hours with a stirring rate of 15 r / min. Finally, 1 mL of oleic acid was added to the reaction mixture as a plasticizer to obtain a non-Newtonian fluid material; the peak storage modulus of the non-Newtonian fluid reached 1.1×10 6 Pa, the peak loss modulus is 8.7×10 4 Pa.
[0075] (2) coating the obtained non-Newtonian fluid material onto the PBO fiber material layer, and then covering the surface of the non-Newtonian fluid material with a PI cover diaphragm, and using a hot pressing process (105° C., 0.6 MPa, and holding time of 600 s) to form a three-layer composite structure;
[0076] Among them, the thickness of the barrier layer is 12μm; the thickness of the non-Newtonian fluid material layer is 4mm; and the thickness of the absorption layer is 0.3mm.
[0077] Example 4
[0078] Boric acid was heated to 180°C and kept warm for 2 hours to prepare pyroboric acid. Pyroboric acid, silicon dioxide and hydroxy silicone oil were then mixed in a mass ratio of 1:1:8 to obtain 125g of the mixture, which was reacted in an oven at 200°C for 3 hours with a stirring rate of 15r / min. Finally, 1mL of oleic acid was added to the reaction mixture as a plasticizer to obtain a non-Newtonian fluid material; there was no obvious elasticity visually.
[0079] Example 5
[0080] The method of Example 1 is followed, except that the obtained non-Newtonian fluid material is coated on the PBO fiber material layer, and then a diaphragm is placed under the PBO fiber material layer, and a three-layer composite structure is made by a hot pressing process (105°C, 0.6MPa, and holding time 600s).
[0081] Comparative Example 1
[0082] The diaphragm and the PBO fiber material layer were made into a double-layer composite structure by hot pressing process (105° C., 0.6 MPa, holding time 600 s).
[0083] Comparative Example 2
[0084] (1) Boric acid was heated to 180°C and kept warm for 2 hours to prepare pyroboric acid. Pyroboric acid, silicon dioxide and hydroxy silicone oil were then mixed in a mass ratio of 1:1:20 to obtain 110 g of the mixture, which was reacted in an oven at 200°C for 3 hours with a stirring rate of 15 r / min. Finally, 1 mL of oleic acid was added to the reaction mixture as a plasticizer to obtain a non-Newtonian fluid material.
[0085] (2) coating the obtained non-Newtonian fluid material onto the surface of the diaphragm, and forming a double-layer composite structure by hot pressing (105° C., 0.6 MPa, holding time 600 s);
[0086] Among them, the thickness of the barrier layer is 12μm; the thickness of the non-Newtonian fluid material layer is 3mm.
[0087] Comparative Example 3
[0088] The method of Example 1 is followed, except that the PBO fiber material layer is immersed in a non-Newtonian fluid material and then taken out and dried; a diaphragm is further covered on the surface of the material, and a three-layer composite structure is prepared by a hot pressing process (105°C, 0.6MPa, and holding time of 600s).
[0089] Test Case
[0090] The soft pack battery uses NCM positive electrode and ternary negative electrode silicon oxide 88125 model battery cell.
[0091] The composite protective layers prepared in the above examples and comparative examples were respectively attached to the outside of the soft-pack battery (so that the barrier layer is in close contact with the battery surface), and then tested. The battery structure after the composite protective layer in the example is as follows: Figure 1 As shown, along the surface of the battery body outward, the composite protective layer includes an optional barrier layer, a non-Newtonian fluid material layer and an absorption layer arranged in sequence.
[0092] 1. Impact test
[0093] A 35 mm stainless steel ball (weight 175 g) was used to impact the soft pack battery to produce an energy impact of 2.06 joules. The sphere was placed vertically 120 cm above the target and fell freely through a 40 mm diameter PVC pipe to impact the battery. The open circuit voltage was monitored by the battery test system.
[0094] The impact absorption capacity of the battery cell during the impact process is calculated according to the impact energy and the absorption energy. The impact absorption capacity test results of the above embodiments and comparative examples are shown in Table 1.
[0095] Impact absorption capacity (%) = absorbed energy Ea / impact energy E×100%.
[0096] The impact energy is calculated by formula (1): E = Mgh.
[0097] In formula (1), E is the potential energy of the object, the unit is J, M is the mass of the object, the unit is kg, g is the acceleration due to gravity, the unit is m / s, and h is the impact height, the unit is m.
[0098] The absorbed energy is calculated by formula (2):
[0099] Mgh=Ea+∫Fdz, Formula (2)
[0100] In formula (2), m is the weight in kg, g is the acceleration due to gravity, h is the impact height in m, Ea is the absorbed energy in J, F is the impact force in N, and z is the penetration depth in m. This formula indicates that when the punch falls from a height, its gravitational potential energy is converted into the material absorbed energy Ea and the work done during the penetration process, that is, ∫Fdz.
[0101] 2. Acupuncture experiment
[0102] Place the sample on a flat surface and use a 1mm diameter steel needle to puncture the battery radially at a speed of 80mm / s. Stop puncturing when the sample deformation is ≥10%. The puncture test results are divided into the following three types:
[0103] pierce:***;
[0104] Stab wounds, no obvious penetration: **
[0105] No puncture damage:*.
[0106] The results of the needle puncture test of the soft-pack battery coated with a single layer of the composite protective layer of Example 1 are as follows: Figure 2 As shown, it can be seen that the surface of the soft-pack battery is not damaged; the results of the soft-pack battery needle puncture test using the composite protective layer of Comparative Example 1 and Comparative Example 2 are respectively as follows Figure 3 and Figure 4 As shown, it can be seen that the soft-pack battery using the composite protective layer of Comparative Example 1 was penetrated by the needle in the needle puncture test, and the soft-pack battery using the composite protective layer of Comparative Example 2 was partially penetrated by the needle. The needle puncture test results of the above embodiments and comparative examples are shown in Table 1.
[0107] Table 1
[0108] Example No. Shock absorption capacity% Acupuncture results Example 1 86 * Example 2 82 * Example 3 80 * Example 4 59 ** Example 5 52 ** Comparative Example 1 21 ** Comparative Example 2 45 ** Comparative Example 3 43 **
[0109] It can be seen from the results in Table 1 that the composite protective layer provided by the present invention can not only improve the impact absorption capacity of the battery body, but also show a synergistic enhancement effect in puncture protection, and can effectively prevent the battery from short circuiting or being damaged when subjected to severe impact or extrusion.
[0110] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composite protective layer for a battery, characterized in that: The composite protective layer comprises an optional barrier layer, a non-Newtonian fluid material layer and an absorption layer which are arranged in sequence, and the absorption layer comprises a fiber-reinforced resin-based composite material.
2. The composite protective layer according to claim 1, wherein: Along the outward direction of the surface of the battery body, the composite protective layer includes an optional barrier layer, a non-Newtonian fluid material layer and an absorption layer which are arranged in sequence.
3. The composite protective layer according to claim 1 or 2, wherein: The thickness ratio of the non-Newtonian fluid material layer to the absorption layer is 1-20:1, preferably 6-14:
1.
4. The composite protective layer according to any one of claims 1 to 3, wherein: The barrier layer is a flexible film, preferably a diaphragm; and / or, the melting point of the barrier layer is not less than 130°C, preferably not less than 180°C, more preferably not less than 200°C; and / or, the barrier layer has a thickness of 0-100 μm, preferably 10-20 μm; and / or, the longitudinal tensile strength MD of the barrier layer is ≥80 Mp, preferably 80-100 Mp; And / or, the transverse tensile strength TD of the barrier layer is ≥50 Mp, preferably 50-100 Mp.
5. The composite protective layer according to any one of claims 1 to 4, wherein: The non-Newtonian fluid material layer includes a non-Newtonian fluid material; And / or, the peak storage modulus of the non-Newtonian fluid material is 1×10 5 -5×10 6 Pa; And / or, the peak loss modulus of the non-Newtonian fluid material is 2×10 4 -3×10 5 Pa; And / or, the thickness of the non-Newtonian fluid material layer is 2-10 mm, preferably 2-6 mm.
6. The composite protective layer according to claim 5, wherein: The non-Newtonian fluid material includes reinforcing particles, pyroboric acid, hydroxy silicone oil and oleic acid; and / or, the reinforcing particles are selected from at least one of silica particles, calcium carbonate, titanium powder, polystyrene and polymethyl methacrylate, preferably silica particles; And / or, the particle size of the reinforcing particles is 0.1-0.5 μm; And / or, the mass ratio of the reinforcing particles, pyroboric acid and hydroxy silicone oil is 1:(0.1-5):5-50, preferably 1:(0.5-2):10-30; And / or, the content of oleic acid is 0.2-2 mL relative to the total amount of 100 g of the reinforcing particles, pyroboric acid and hydroxy silicone oil.
7. The composite protective layer according to any one of claims 1 to 6, wherein: The density of the fiber-reinforced resin-based composite material is 1.2-2.2 g / cm 3 ; And / or, the fiber-reinforced resin-based composite material has a tensile strength of 4-10 GPa and a modulus of 100-300 GPa; And / or, the fiber-reinforced resin-based composite material is at least one of PBO fiber, glass fiber, and carbon fiber; And / or, the absorption layer has a thickness of 0.1-10 mm, preferably 0.1-1.5 mm.
8. The method for preparing the composite protective layer for a battery pack according to any one of claims 1 to 7, comprising: The non-Newtonian fluid material is coated on the surface of the absorption layer, and then a barrier layer is optionally compounded on the surface of the non-Newtonian fluid material, and then the whole is heat-pressed.
9. The preparation method according to claim 8, wherein: The preparation method of the non-Newtonian fluid material comprises: first mixing the reinforcing particles, pyroboric acid, and hydroxy silicone oil under stirring conditions, and then second mixing with oleic acid; and / or, the temperature of the first mixing is 150-300°C, preferably 180-260°C; And / or, the first mixing time is 60-480 min, and the stirring speed is 5-200 r / min.
10. A method for improving the impact resistance of a battery body, comprising: Compounding the composite protective layer for a battery according to any one of claims 1 to 7 on the outer surface of the battery body; Preferably, the battery body is a battery cell, a soft-pack battery, a battery module or a battery PACK.
Citation Information
Patent Citations
Shear thickening fluid based on molecular colloid and preparation method and application of shear thickening fluid
CN102926211A
Preparation method and application of thermal-insulation shear thickening fluid composite three-dimensional fabric
CN108867078A
Non-Newtonian fluid impregnated grid enhanced hydrogen storage pressure vessel structure and process
CN112344200A
Fiber-reinforced resin-based composite material based on shear thickening fluid and preparation method of fiber-reinforced resin-based composite material
CN118599288A
Battery cell, battery, battery pack and electric equipment
CN221176415U